IMPACT OF THE GLBOAL CRISIS ON LABOR MARKETS AND UNEMPLOYMENT IN SLOVAK REPUBLIC - Martincova, Marta (European Scientific Journal, ESJ, 2014)
Defining demand at a national level is problematic in terms of the total volume of the structure, as to the performance of transnational corporations. Reviving of unemployment can not only be assessed at the national level, but an important aspect affecting national labor market is the revival of global economy which leads to the growth of the global labor needs. Currently, the focus of new jobs is shifting from partial professions towards cross-cutting and systemic professions, which must give a comprehensive response to developments in a particular industry. Slovakia is a small market economy significantly tied to major European economies, dominated by linkage to the German economy. Due to the high openness of the economy, the crisis has significantly affected the rate of growth of country’s performance and caused a drop in demand, a decrease in both production and unemployment. High unemployment in this period was related to revenue shortfalls in the state budget and deepening of the budget deficit.